Effects of causeway construction on environment and biota of subtropical tidal flats in Okinawa, Japan. Issue 1 (15th May 2015) - Reimer, James Davis; Yang, Sung-Yin; White, Kristine N.; Asami, Ryuji; Fujita, Kazuhiko; Hongo, Chuki; Ito, Shingo; Kawamura, Iori; Maeda, Isshu; Mizuyama, Masaru; Obuchi, Masami; Sakamaki, Takashi; et al.
Highlights: Comprehensive analyses of impact of road construction on subtropical tidal flats. 7/10 sites had evidence of large reduction of water flow from analyses of cores. One site (=S1) had poor water quality, reduced biodiversity; outlier in all analyses. At site S1, enterobacterial Serratia and amphipod Corophium sp. dominated. Temperature, water quality did not appear to cause differences between/among sites. Abstract: Okinawa, Japan is known for its high marine biodiversity, yet little work has been performed on examining impacts of numerous large-scale coastal development projects on its marine ecosystems. Here, we examine apparent impacts of the construction of the Kaichu-Doro causeway, which was built over 40 years ago. The causeway is a 4.75 km long embankment that divides a large tidal flat and has only two points of water exchange along its entire length. We employed quadrats, transects, sampling, visual surveys, and microbial community analyses combined with environmental, water quality data, and 1 m cores, at five stations of two paired sites each (one on each side of Kaichu-Doro) to investigate how the environment and biota have changed since the Kaichu-Doro was built. Results indicate reduction in water flow, and site S1 was particularly heavily impacted by poor water quality, with low diversity and disturbed biotic communities.